Stress at work: The case of municipal police officers - Cieślak, Ilona (Work, 2020)
INTRODUCTION AND OBJECTIVE: Occupational stress-related factors among working municipal police officers in Poland have not been examined in the literature. The purpose of the paper was to evaluate the impact of selected work-related factors on occupational stress in active municipal police officers in Warsaw by using configural frequency analysis (CFA). MATERIALS AND METHODS: A cross-sectional study was conducted among 578 participants, which accounted for 55.1% of all municipal police officers in Warsaw. The majority of study participants were men (72%) (mean age 43 years old). Two groups of workplace-related stress factors were analysed in the study: physical conditions and organisational working conditions causing stress. The study was carried out using the PAPI method (Paper-and-Pencil Interviewing), based on a proprietary questionnaire developed for the study. CFA searches for templates and patterns in contingency tables. RESULTS: Municipal police officers who claimed that stress did not affect health, took advantage of psychological/psychiatric advice less often than those who thought so (1.7% vs 10.1%; χ2 = 20.152, df = 2, P = 0.000). Those who declared that they often experienced stress at work were also more prone to claiming that one or two factors affected their level of stress: physical abuse, contact with infectious materials, working at uncomfortable temperatures or working in a noisy environment. In the opinion of the study population, there were some factors which contributed to the occurrence of stress at work, and these factors included: working in a hurry, lack of necessary resources, devices and materials at work, the need to be available at all times and the unpredictability of the work. The municipal police officers from the study population combined two or three methods to cope with stress, such as watching TV, surfing the Internet and talking with their families. CONCLUSION: Due to the specificity of a municipal police officer’s occupation, special attention should be paid to the occupational stress risk factors characteristic for this group of professionals, and measures should be taken to reduce the number of stressors. It is important to organise training events devoted to effective methods of coping with stress. There is need to carry out more in-depth studies of occupational stress among municipal police officers.